1997
DOI: 10.1006/geno.1996.4541
|View full text |Cite
|
Sign up to set email alerts
|

The Gene for Pendred Syndrome Is Located between D7S501 and D7S692 in a 1.7-cM Region on Chromosome 7q

Abstract: P a u l C o u c k e , * G u y V a n C a m p , * '1 O sm a n D em irhan,+ Y ilm a z K a b a k k a y a^ W e n d y B a le m a n s ,* P e te r V a n H a u w e , * T o m V a n A g t m a e l, * R ich a rd J. H. Sm ith , § A g n e te P a rv in g , C u n y H, H. M. Bolder,!! C o r W. R. J. Cremers,|| a n d P a t ric k J. W ille m s *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Pendred syndrome is an autosomal recessive disease originally described as being associated with congenital deafness and goiter (Pendred 1896). Recent advances in molecular genetics have revealed that the responsible gene is localized in 7q31 (Coucke et al 1997), and that the PDS gene (PDS ), the gene responsible for Pendred syndrome, is mutated in the patients (Everett et al 1997).…”
Section: Shin-ichi Usami · Satoko Abe · Mike D Weston Hideichi Shinkmentioning
confidence: 99%
“…Pendred syndrome is an autosomal recessive disease originally described as being associated with congenital deafness and goiter (Pendred 1896). Recent advances in molecular genetics have revealed that the responsible gene is localized in 7q31 (Coucke et al 1997), and that the PDS gene (PDS ), the gene responsible for Pendred syndrome, is mutated in the patients (Everett et al 1997).…”
Section: Shin-ichi Usami · Satoko Abe · Mike D Weston Hideichi Shinkmentioning
confidence: 99%
“…However, the majority of patients remain euthyroid [13]. It is now widely acknowledged that mutations in the gene SLC26A4 located on chromosome 7q21-34 [14,15] are involved in the presentation of an EVA/PDS phenotype [14,16,17]. Biallelic mutations in the gene SLC26A4 have been shown to cause Pendred syndrome, accounting for its autosomal recessive inheritance [9,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Family 8 showed critical recombination in D7S501 (centromeric boundary), and the recombinant detected in Family 10 excluded the telomeric region from D7S2425. This region overlaps that for Pendred syndrome [Sheffield et al, 1996;Coyle et al, 1996;Gausden et al, 1997;Coucke et al, 1997], DFNB4 [Baldwin et al, 1995], and DNFB13 [Mustapha et al, 1998]. Thus, four different disorders have so far been mapped to the same region.…”
Section: Discussionmentioning
confidence: 82%